HOTS-AEP-COVID-19 and ILMIZI learning model: The 21st-Century environmental learning in senior high school - Ilmi Zajuli Ichsan; Henita Rahmayanti; Agung Purwanto; Diana Vivanti Sigit; Mieke Miarsyah; Paulo Weslem Portal Gomes (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Environmental learning in the Coronavirus Disease 2019 (COVID-19) pandemic requires 21st-Century learning innovation which promotes Higher-Order Thinking Skills (HOTS) of which ILMIZI is the potential learning model. The purpose of this study was to measure the students’ HOTS using HOTS Assessment based on Environmental Problem of COVID-19 (HOTS-AEP-COVID-19) and describe the syntax of ILMIZI model for the implementation of e-learning during the COVID-19 pandemic. The research subjects used  were 172 senior high school students randomly selected from Bekasi City in several schools. The descriptive research used online survey as the data collection technique. The results showed that the students HOTS scores measured using HOTS-AEP-COVID-19 were still in very low category either for all students (22.83) or male students (21.32) and female students (23.82). Hence, the ILMIZI model need further evaluation to be implemented as an alternative for the 21st-Century environmental learning.